A comparison of field assessment methods for lucerne inoculation experiments. (31st December 2022) - Tang, Lin; Morel, Julien; Halling, Magnus; Öhlund, Linda; Parsons, David
ABSTRACT: Effective and practical measurement methods for assessing field inoculation experiments are needed to identify inoculants that could improve lucerne establishment. In this study, assessment potential of different existing measurement methods (plant height, Dualex 4 Scientific leaf-clip meter, GreenSeeker handheld crop sensor, drone-acquired orthomosaic calculation, yield, nutrient analysis and nodule assessment) were compared across 12 inoculation treatments applied to lucerne ( Medicago sativa L.) at 3 sites. F -values were used to compare the potential of different methods to separate inoculation treatments. The handheld GreenSeeker measuring normalised difference vegetation index (NDVI) showed the greatest potential for separating inoculation treatments in fields where lucerne had not previously been cultivated, followed by visible atmospherically resistant index (VARI) and green-red vegetation index (GRVI) from drone-acquired orthomosaics. These methods are non-destructive, low cost, require low labour input, fast, and do not require sample preparation, and thus are efficient measurement methods for disaggregating treatments in field inoculation experiments.